Розробка графічного інтерфейсу користувача в галузі біомедичної інженерії - Оржинська, М. С. (Издательство «Точка», 2017)
This is a review article in which I will tell you about the advantages and disadvantages of the graphical user interface in the field of biomedical engineering. It also shows the types of modern graphical interfaces and what they should be from the point of view of the user, in this case - the patient.
Keywords: графічний интерфейс